If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 2)(6x + -10)(x + 20) = 180 Reorder the terms: (2 + 5x)(6x + -10)(x + 20) = 180 Reorder the terms: (2 + 5x)(-10 + 6x)(x + 20) = 180 Reorder the terms: (2 + 5x)(-10 + 6x)(20 + x) = 180 Multiply (2 + 5x) * (-10 + 6x) (2(-10 + 6x) + 5x * (-10 + 6x))(20 + x) = 180 ((-10 * 2 + 6x * 2) + 5x * (-10 + 6x))(20 + x) = 180 ((-20 + 12x) + 5x * (-10 + 6x))(20 + x) = 180 (-20 + 12x + (-10 * 5x + 6x * 5x))(20 + x) = 180 (-20 + 12x + (-50x + 30x2))(20 + x) = 180 Combine like terms: 12x + -50x = -38x (-20 + -38x + 30x2)(20 + x) = 180 Multiply (-20 + -38x + 30x2) * (20 + x) (-20(20 + x) + -38x * (20 + x) + 30x2 * (20 + x)) = 180 ((20 * -20 + x * -20) + -38x * (20 + x) + 30x2 * (20 + x)) = 180 ((-400 + -20x) + -38x * (20 + x) + 30x2 * (20 + x)) = 180 (-400 + -20x + (20 * -38x + x * -38x) + 30x2 * (20 + x)) = 180 (-400 + -20x + (-760x + -38x2) + 30x2 * (20 + x)) = 180 (-400 + -20x + -760x + -38x2 + (20 * 30x2 + x * 30x2)) = 180 (-400 + -20x + -760x + -38x2 + (600x2 + 30x3)) = 180 Combine like terms: -20x + -760x = -780x (-400 + -780x + -38x2 + 600x2 + 30x3) = 180 Combine like terms: -38x2 + 600x2 = 562x2 (-400 + -780x + 562x2 + 30x3) = 180 Solving -400 + -780x + 562x2 + 30x3 = 180 Solving for variable 'x'. Reorder the terms: -400 + -180 + -780x + 562x2 + 30x3 = 180 + -180 Combine like terms: -400 + -180 = -580 -580 + -780x + 562x2 + 30x3 = 180 + -180 Combine like terms: 180 + -180 = 0 -580 + -780x + 562x2 + 30x3 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-290 + -390x + 281x2 + 15x3) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-290 + -390x + 281x2 + 15x3)' equal to zero and attempt to solve: Simplifying -290 + -390x + 281x2 + 15x3 = 0 Solving -290 + -390x + 281x2 + 15x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5v-8=-53 | | 200-(-400)= | | J(u-w)=t | | X^2-14x-234=0 | | 6v(4v-8)= | | 70=.28*x | | 49b^2=256 | | 3x^2+10x+8=-2 | | 4[x-5]=-3[x-5] | | 3a+12b+15= | | 9[7-(7x-9)]+6x=0 | | -2x+24=0 | | 12x+-9+62+-3x+16x+2=180 | | 4x*2=49 | | 8(x-3)+5=8x+7 | | 3(2z-6)-4(3z+1)=5-2(2+1) | | 6x+3y+9x+y= | | 3n+4=8n-1 | | 4(2w+3)+2(3+w)= | | 4(w-6)=3(a+1) | | 7x+13=2x+8 | | -21+7y=9x | | 58-2+7=8x | | 3a+34b= | | 0.1x=.2(2+x) | | 2(b+5)+6b=5b+2b+1 | | 4x-13x+10=0 | | -10h=-6(4+3h) | | .5xn=.333 | | 6x+2y=16.60 | | 4(5)-4x=4 | | -4k(k+6)-(9k-6)=-14k |